(untitled) (European Journal of Interdisciplinary Research and Development, 2025)
Children are particularly vulnerable to environmental contaminants due to their ongoing growth, metabolic immaturity, and higher food intake per unit body weight compared to adults. Among these contaminants, trace amounts of pesticide residues in food have raised increasing concern because of their potential long-term effects on child health. Although pesticide levels detected in food products often remain below established safety thresholds, chronic exposure to low doses may pose cumulative and developmental risks that are not fully captured by conventional toxicological assessments. This article aims to evaluate the risk associated with dietary exposure to microquantities of pesticides in children. Special attention is given to exposure pathways, age-related susceptibility, metabolic and neurodevelopmental effects, endocrine disruption, and immune system modulation. Current approaches to pesticide risk assessment, including acceptable daily intake and cumulative risk evaluation, are critically analyzed in the context of pediatric health. Understanding the potential impact of chronic low-level pesticide exposure is essential for improving food safety regulations, refining risk assessment models, and developing effective strategies to protect child health.